ETHNOBOTANICAL STUDY OF MEDICINAL PLANTS BASED ON LOCAL KNOWLEDGE IN SEDAYU VILLAGE, JUMANTONO, KARANGANYAR - Agustina, Ana; Rahmatika, Aulia; Masyithoh, Galuh (SEAMEO BIOTROP, 2024)
Medicinal plants are one of the important aspects of traditional medicine development. The utilization of medicinal plants is a very valuable local wisdom and a culture that needs to be investigated more thoroughly so that knowledge about it does not become extinct. The purpose of this study is to determine the plant species that were used, the parts of plants that were used, and how to process them. This research was conducted in May 2023 in Sedayu Village, Jumantono District, Karanganyar Regency. The informants of this research were the people of Sedayu Village. The method used was snowball sampling which focuses on the community of medicinal plant users. The collected data was descriptively qualitatively and quantitatively assessed. The results showed that there were 52 species of medicinal plants used by the Sedayu Village community including ginger, kencur, turmeric, red betel, and ciplukan. The most utilized part of medicinal plants was the leaves and the most common processing method was boiling and drinking. With this information, it can be a reference for the village government and the community regarding how important a type of plant as a medicine to be preserved.